Immediate implant placement following tooth extraction with simultaneous lateral sinus augmentation: a retrospective clinical study after at least 1 year of loading - Bok-Joo Kim; Chul-Hoon Kim; Jung-Han Kim (SpringerOpen, 2021)
Abstract Background Lateral sinus augmentation is necessary when the residual bone height is insufficient in the posterior maxilla. Immediate implant placement following tooth extraction with lateral sinus augmentation will shorten the number of operations and treatment time. Purpose To evaluate radiologic and clinical results for at least 1 year after loading in patients who underwent tooth extraction, implant placement, and lateral sinus augmentation at the same time. Materials and methods We retrospectively evaluated 35 implants placed in 25 patients. Preoperative and postoperative CBCT were compared and analyzed for residual bone height (RBH) and increased bone height (IBH), the initial torque value (ITV), and the implant stability quotient (ISQ). A comparative evaluation was performed between a 1-stage (non-submerged) group and a 2-stage (submerged) group. After loading for at least 1 year, clinical and radiological evaluations were performed to evaluate the survival rate. Results One of the 35 implants failed in osseointegration, and the remaining 34 showed successful results. The failure-free survival rate at 1 year was 97.06% (95% CI, 91.38-100.0%). The RBH ranged from 3.1 to 9.6 mm (mean, 5.62 ± 1.68 mm), and the IBH ranged from 3 to 15.3 mm (mean, 8.87 ± 2.74 mm). Among the RBH, ITV, ISQ, treatment period, final bone height, and failure evaluation by stage of implant placement, only ISQ showed statistical significance between the groups (p < .001). A comparison of RBH, ITV, and ISQ, regardless of group, showed that each value tended to increase, but there were no statistically significant differences. Conclusions Immediate implant placement following tooth extraction with simultaneous lateral sinus augmentation is considered reliable even though the procedures had been performed at the same time.